2010
DOI: 10.1177/1043986209359557
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Bullying, Cyber Bullying, and Deviance: A General Strain Theory Approach

Abstract: Agnew’s general strain theory (GST) has received significant empirical attention, but important issues remain unresolved. This study addresses three such issues. First, the authors examine the effects of bullying—a source of strain that may be consequential, but that has been neglected in GST research to date. Second, drawing from recent research on deliberate self-harm among adolescents, the authors examine the effects of bullying not just on externalizing deviance (aggressive acts committed against others an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(130 citation statements)
references
References 41 publications
5
123
0
2
Order By: Relevance
“…Those articles which shared study populations were: Schenk et al [28] and Schenk et al [29]; Bauman et al [30] and Romero et al [31]; Alavi et al [32] and Roberts et al [33]; Cénat et al [34] and Hébert et al [35]; Hay and Meldrum [14] and Hay et al [36]; and Messias et al [37], Reed et al [38], and Kindrick et al [39]. Further details of these study populations are available in Supplementary Material 1.…”
Section: Study Populationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Those articles which shared study populations were: Schenk et al [28] and Schenk et al [29]; Bauman et al [30] and Romero et al [31]; Alavi et al [32] and Roberts et al [33]; Cénat et al [34] and Hébert et al [35]; Hay and Meldrum [14] and Hay et al [36]; and Messias et al [37], Reed et al [38], and Kindrick et al [39]. Further details of these study populations are available in Supplementary Material 1.…”
Section: Study Populationsmentioning
confidence: 99%
“…Excluding duplicate populations [29,31,32,34,36,38,39], the total number of unique participants was 155,471, with a mean of 6,478 and median of 2,761 individuals per study. Most studies included both female and male participants (often not reported separately).…”
Section: Study Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cross-sectional research suggests that the perpetration of face-to-face bullying and cyberbullying are associated with problem behaviours such as poor academic achievement (Mitchell, Ybarra, & Finkelhor, 2007), drinking alcohol (Mitchell et al, 2007), smoking and other substance use problems (Niemelä et al, 2011), vandalism (Hay, Meldrum, & Mann, 2010), stealing (Hay et al, 2010), intentionally hurting other people (Hay et al, 2010), weapon-carrying (Dukes, Stein, & Zane, 2010) and other delinquent behaviours.…”
Section: Introductionmentioning
confidence: 99%